PERSEUS' DESIRE TO BE HUMAN IN LOUIS LETERRIER'S CLASH OF THE TITANS (2010) MOVIE: A PSYCHOANALYTIC APPROACH - WARDANI, DHIMAS KUSUMA (2011)
This study is aimed to show the Perseus' desire to be human in Clash of the Titans movie by using a psychoanalytic approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the psychoanalytic approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Clash of the Titans movie directed by Louis Leterrier released in 2010. While the secondary data sources are other materials taken from literary books, criticism, and some articles related to the movie. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, editing, point of view, mise en scence, cinematography, and sound are related to each other and form unity to be good quality of a movie. Second, based on the psychoanalytic approach, Louis Leterrier represents of the desire to be human. The character of Perseus has desire to be human than to be God, although he is a son of Zeus.